The Sword In The Stone - Storr, Catherine; Hunter, Susan (Milwaukee : Raintree Childrens Books, 1985)
A brief retelling of selected parts of the Arthurian legend.
Keywords: Arthur, -- King; Arthurian romances; Knights and knighthood -- Fiction; Folklore -- England